Determining Pain Assessment and Management Practices of Surgical and Critical Care Nurses - İbrahim Hantsi; Ümran Dal Yılmaz (Mediterranean Nursing and Midwifery, 2022)

(untitled)
Objective:The aim of this study is to determine the pain assessment and management practices of surgical and critical care nurses.Method:This descriptive cross-sectional study was conducted at Specialist Hospital Sokoto in March 2021. A total of 148 surgical and critical care nurses voluntarily participated in this study. Data were collected using questionnaires. The statistical analysis was performed by Statistical Package for Social Science. Descriptive statistics were used in data analysis.Results:The result of the study showed that nurses had a high level of awareness of all domains of pain assessment and management practices; however, the barriers to practice were too high.Conclusion:Based on the results of the study, development of policies to ensure that pain scores and management are discussed during handling and taking over ward rounds, continuous education, providing any course/training on surgical pain management, and assessment to improve nurses’ knowledge and practices.